FRI0649 Standardized procedures for ultrasound imaging in paediatric rheumatology: progress of a eular task force. (15th June 2017) - Janta, I; Ramos, P Collado; Vojinovic, J; Naredo, E; Carmona, L
Abstract : Background: Musculoskeletal ultrasound (MSUS) is a useful imaging technique in paediatric rheumatic diseases (PRD). US has several advantages over other imaging techniques: it is non-invasive, radiation free, rapid, highly accepted by the patients and does not require sedation for scanning in younger children. However, MSUS examination is incriminated to be an operator dependent technique. Moreover, the variability of normal sonoanatomy in children, due to ossification, makes the acquisition and interpretation of MSUS images difficult. The variability in background and experience of ultrasonographers in different countries requires an international multidisciplinary effort for an optimal standardization of MSUS performance in PRD. Objectives: To perform a systematic literature review on guidelines for MSUS for children published by international societies and articles on how to perform MSUS scanning in children. This represents the first step for an EULAR taskforce, which objective is to develop EULAR Standardized Procedures for Ultrasound Imaging in Pediatric Rheumatology through a consensus process among rheumatologists, paediatric rheumatologists, and radiologists highly experienced in the performance, teaching and research in paediatric MSUS in rheumatologic disease. Methods: The objective was reformulated according to the PICO-adapted approach, as follows: body parts, ultrasound, and scanning procedures. For each component several synonyms were used. Search limits were applied for animal studies and age. The literature search was performed in Medline and Embase from databases inception to 1st June 2016. References identified were imported into a bibliographic manager and duplicates were removed. To identify eligible studies the remaining articles were assessed by title and abstract. Only articles in English were retained. From the selected studies, data about the examined area, patient position, probe placement, scanning method, landmarks and pathologies using a predefined data collection form. Results: The literature search resulted in 6059 articles, of which 4856 were captured in Medline and 1203 in Embase. Figure 1 shows the the study flow-chart for article selection. After removing duplicates and scanning titles and abstracts, 295 articles remained for detailed review. After full-text review, 107 articles were excluded. The main reason for article exclusion after full-text review was the lack of standardized examination. Of the remaining articles, 2 described shoulder structures, 14 elbow structures, 5 wrist structures, 9 hand structures, 25 hip structures, 41 knee structures, 14 ankle structures and 2 foot structures. The number of structures described for each joint part was as follows: 3 shoulder, 13 elbow, 2 wrist, 4 hand, 7 hip, 25 knee, 14 ankle, 1 foot. Conclusions: Several anatomical structures are lacking standardized MSUS examination in children. Disclosure of Interest: None declared